Analisis Kelayakan Usaha Pengemasan Minyak Goreng Kelapa Sawit PT Java Agri Sukses Makmur - Fina Alfiani; Imroatul Afwa; Galuh Ayu Wandira; Irine Selviana Alda; Amilia Susanti; Sri Widayanti (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
There are two types of cooking oil circulating in the community, namely bulk and packaged cooking oil. PT Jawa Agri Sukses Makmur is a branded cooking oil packaging company with the trademarks Sayana, Master Chef and Minyakita. The strategy to be able to compete with other similar companies is to provide a good image through packaging. The aim of this research was to analyze the feasibility of a cooking oil packaging business. The method used is R/C ratio analysis. The research results show that the business is feasible to run as a business seen from the ratio value of 1.05 which indicates the business is feasible and profitable. The company received revenue of IDR 16,508,585,000 and revenue of IDR 1,602,241,754 in one period (one month).